Depression and Endothelial Dysfunction in Psoriatic Arthritis: Is There Any Possible Relationship? - De Lorenzis, Enrico; Di Giorgio, Angela; Natalello, Gerlando; Nesci, Antonio; Tanti, Giacomo; Rubortone, Pietro; Lucchetti, Donatella; Magurano, Maria Rosaria; Di Mario, Clara; Tolusso, Barbara; Peluso, Giusy; Santoliquido, Angelo; et al. (Frontiers in Medicine, 2021)
Background: Cardiovascular events (CVEs) are the first cause of death in patients with psoriatic arthritis (PsA). Depression is a recognized risk factor in cardiovascular events and is frequently associated with PsA. Flow-mediated dilatation (FMD) is a widely used method for assessing endothelial dysfunction, a parameter with strong prognostic implications for CVEs. The study aims to explore the relationship between FMD, depressive symptoms and serum cytokines in a cohort of patients with PsA. Patients and methods: FMD was assessed in 50 consecutive PsA patients aged between 30 and 75 years without known cerebrovascular and coronary heart disease or diabetes. Depressive symptoms were reported using the related sub-scale of the Hospital Anxiety and Depression Scale (HDS). Disease features, activity indexes, adjusted Framingham risk score (aFRS) were calculated. Serum level of IL-6, TNF-α and IL-17A were also assessed. Results: In PsA patients (age 50.7±10.2 years, male 42%, disease duration 5.9±3.3 years, Disease Activity in PSoriatic Arthritis (DAPSA) score 14.0±9.4) FMD inversely correlated to the severity of depressive symptoms according to HDS (ρ=-.339, p=.016), age (ρ=-.507, p =.001), aFRS (rs=-.453, p<.001), duration of PsA (ρ=-.507, p=.001), intensity of pain (ρ=-.507, p=.001) and DAPSA (ρ=-.507, p=.001). No statistically significant correlation was found between FMD or HDS and serum cytokines concentrations. HDS predicted FMD in a model adjusted for age, aFRS, PsA duration and pain intensity (β=-.271, p=0.008), with depressive symptoms contributing directly to 6.4% of the variance. Conclusions: Depressive symptoms correlate with endothelial dysfunction with an exposure-response pattern in our cohort of PsA patients.